This is where you belong [large type]: the art and science of loving the place you live - Warnick, Melody (Thorndike Press large print lifestyles., 2016)
Recounts how the author's family moved multiple times throughout the country before she decided to adopt their latest town as a permanent home by identifying reasons to love it, sharing her findings about the psychology of place attachment and the motivations of people dedicated to improving their cities. --Publisher's description.